The prognostic significance of PD-L1 expression in patients with glioblastoma: A meta-analysis - Guo, Xin; Zhang, Yuelin; Jiao, Hengxing; Miao, Xingyu (Frontiers in Oncology, 2022)
Abstract: Background: Glioma, a malignant brain tumor, has a high morbidity and mortality, with an extremely poor prognosis. In recent years, there has been a lot of studies on the prognosis of gliomas such as PD-L1, but the conclusions are controversial. The relevant literature was reviewed and a meta-analysis was performed to clarify the relevance between PD-L1 expression and OS in glioma. METHODS：The PubMed, Metstr, Cochrane and Web of Science databases were searched for non-foundational literature on PD-L1 expression related to OS in glioma up to February 2022, and the literature was rigorously screened according to inclusion and exclusion criteria, and a random-effects model was used in stata version 16.0 to calculate the total HR and corresponding 95% confidence intervals. RESULTS：Using stata version 16.0 combined with HR and corresponding 95% confidence intervals showed that high/positive expression of PD-L1 in glioma was dramatically related to OS (HR=1.15,95% CI:1.08-1.23, p=0.000). Subgroup analysis also showed that high/positive expression of PD-L1 in glioma or glioblastoma was significantly related to OS (glioma. HR=1.43;95%CI:1.20-1.66, P=0.000; GBM:HR=1.12;95%CI:1.04-1.20, P=0.000); Furthermore, protein and gene subgroup analyses showed that high PD-L1 expression in gliomas was not related to OS in protein metrics (HR=1.09;95% CI:0.92-1.26, P=0.000), but there was a dramatical line of relation in gene metrics (HR=1.17;95% CI:1.08-1.25, P=0.000), a finding no different results from previous studies. CONCLUSION: In gliomas, PD-L1 expression is clearly associated with OS, but this result needs to be interpreted with caution and requires clinical studies in a large amount of patients, in multiple centers, with similar baseline data, with a view to further evaluation.